2000
DOI: 10.1111/1467-8624.00225
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Learning in Children Is Not Related to Age: Evidence from Drawing Behavior

Abstract: Three experiments are reported on implicit learning in 432 children between the ages of 4 and 10 years, using a new paradigm ("the neutral parameter procedure") based on drawing behavior. The first two experiments demonstrated that children modified their drawing behavior following specially devised practice in such a way that these modifications could not be viewed as the result of deliberate adaptive strategies. The third experiment showed that these behavioral modifications lasted for at least 1 hr after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
4
11

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 59 publications
5
48
4
11
Order By: Relevance
“…Theoretically, this heuristic system would be relatively independent of general intelligence and age (Reber, 1993;Stanovich, 1999), as the unconscious and implicit processes on which it relies (Vinter & Perruchet, 2000). However, many studies using tasks issued from the ''heuristic and biases" literature have provided evidence that the heuristic system increases in efficiency with age.…”
Section: The Development Of the Two Systems Of Reasoningmentioning
confidence: 99%
“…Theoretically, this heuristic system would be relatively independent of general intelligence and age (Reber, 1993;Stanovich, 1999), as the unconscious and implicit processes on which it relies (Vinter & Perruchet, 2000). However, many studies using tasks issued from the ''heuristic and biases" literature have provided evidence that the heuristic system increases in efficiency with age.…”
Section: The Development Of the Two Systems Of Reasoningmentioning
confidence: 99%
“…First, it has been demonstrated that this kind of learning is based on processes that remain unaffected by developmental differences and, thus, is perfectly efficient in preschoolers (Meulemans, Van der Linden, & Perruchet, 1998;Vinter & Perruchet, 2000; but see Maybery, Taylor, & O'Brien-Malone, 1995). Second, the studies evoked above indicate that people can become sensitive to subtle environmental regularities such as frequent co-occurrences and perhaps syntactic rules.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that implicit learning emerges early in development and shows few effects of age. Many authors have alluded to this idea (e.g., Beek, 2000;Bertenthal, 1996;Vinter & Perruchet, 2000). Bertenthal (1996), for instance, holds that "with exploration of their own actions and the environment, infants show increasing sensitivity to perceptual changes and finer control of actions that are guided by this information.…”
Section: Introductionmentioning
confidence: 99%